Places of fear and attachment. How Azoreans perceive seismic and volcanic risk. - Rego, Isabel Estrela (2013)
Copyright © 2012 Global Journal of Community Psychology Practice by GJCPP Editorial Board is licensed under a Creative Commons Attribution-NonCommercial-NoDerivs 3.0 Unported License.